Fear Of Missing Out (FoMO) Mediates Live Shopping Effects On Gen-Z Impulsive Buying - Putri Arizka; Dwi Kiki Enjela; Anita Ade Rahma (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to analyze the influence of live shopping on impulsive buying with Fear of Missing Out (FoMO) as a mediating variable in Generation Z consumers. This research is based on the theory of Stimulus–Organism–Response (S-O-R) which explains that external stimuli can affect an individual's psychological state and induce certain behavioral responses. The research approach used is quantitative with a survey method. Data was collected through an online questionnaire distributed to 150 Generation Z respondents in Padang City who had experience participating in live shopping. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the help of SmartPLS 4 software. The results of the study show that live shopping has a positive and significant effect on Fear of Missing Out and impulsive buying. In addition, Fear of Missing Out also has a positive and significant effect on impulsive buying. Other findings suggest that Fear of Missing Out acts as a mediating variable in the relationship between live shopping and impulsive buying. These results indicate that impulse buying behavior in the context of live shopping is not only influenced by marketing stimuli, but also by consumers' emotional and psychological responses.